Depression, Anxiety, and Stress in Post-Burn Patients and its Association with Self-esteem and Social Support: A Cross-sectional Study - Triveni M. Gowdar; Harshitha V. Handral; G. Archana; K. T. Ramesha (Journal of Psychiatry Spectrum, 2025)
Background: A burn injury is a traumatic experience that subjects survivors to intense stress and can lead to significant physical, cosmetic, and psychological effects. Reduced self-esteem adversely affects how burn patients interact with others, emotions, and overall functioning. Social support is crucial in improving the mental well-being of individuals recovering from burns. Aim: The aim of this study was to assess the frequency of depression, anxiety, and stress in post-burn patients and to determine their association with self-esteem and social support. Materials and Methods: Using the criterion sampling, participants were selected in a tertiary care hospital. Assessment tools include Depression, Anxiety, and Stress Scale-21, Rosenberg’s Self-Esteem Scale, and Multidimensional Scale of Perceived Social Support (MSPSS). Results: Among the participants, 5.3% had moderate depression, 6.4% had moderate anxiety, and 8.5% experienced moderate stress. Additionally, 95% demonstrated good self-esteem, while 83% reported high social support. A significant negative correlation was observed between self-esteem and both depression (P < 0.0001) and stress (P < 0.0001). A significant negative correlation was found between depression and total perceived social support (PSS; P < 0.0001). Negative correlation was found between anxiety and total PSS. Negative correlation was found between stress and total PSS. Conclusion: The study highlights that good self-esteem and high social support reduces depression, anxiety, and stress in burn patients. This suggests that interventions targeting at improved social support networks and enhancing self-esteem can reduce the burden in burn patients and thereby improve the functional outcome.